Harry hates shopping! - Armitage, Ronda; Armitage, David, 1943- (New York : Scholastic, 1992)
Mother Koala must get the upper hand when her two children Harry and Matilda quarrel during a shopping trip.
"Cartwheel books"
"Grades 1 & 2 Ages 6-8"--Cover p. [4].
450
Accelerated Reader AR
Keywords: Koala -- Fiction; Brothers and sisters -- Fiction; Behavior -- Fiction; Shopping -- Fiction